Guest Editorial: Nanopackaging Part II - Attila Bonyar; Brajesh Kumar Kaushik; James E. Morris; Markondeyaraj Pulugurtha (IEEE Open Journal of Nanotechnology, 2022)
The papers in this special section focus on nanopackaging. It begins with three reviews of diverse nanoscale technologies and then moves on to research papers focused primarily on nanomaterials for on-chip interconnect and noise abatement.